A Study of Metaphor in A Thousand Splendid Suns from Conceptual Metaphor Perspective - Matin, Fawad; Sultani, Mohammad Ebrahim; Anwari, Jawad (Farah Research and Scientific Journal, 2025)
The present investigation is designed to study English metaphors based on the conceptual metaphor theory within the cognitive linguistics framework. From cognitive linguistic view metaphor is not only a rhetorical device but a cognitive instrument which is pervasive in language action and thought. Khaled Hosseini’s novel, A Thousand Splendid Suns, disapproves the false notion of incompetency of third world women to struggle for their own rights. Despite all the pressure, the resisting practices are apparent in the actions of two major female characters of the novel. the objectives of this study is to show how metaphors are linked to the use of a particular language, thought and culture and intend to answer the following research questions: What are the source domain metaphors used in A Thousand Splendid Suns? Which source domain metaphor is the more frequent in A Thousand Splendid Suns? The author identifies metaphors in A Thousand Splendid Suns under the guidance of Metaphor Identification Procedures Vrije University (MIPVU), categorizes metaphors prove the conceptual metaphors after an in-depth analysis of their mapping routines and summarizes their distinct features. The result come out into eight types according to different source domain metaphors, such as human activities metaphor, the human body metaphor, journey metaphor, building metaphor, orientation metaphor, animal metaphor, war metaphor, and plant metaphor, thus human activity metaphor have been used for (46) times and takes the highest position of metaphorical expressions while building metaphor have been used for (5) times, which is positioned the lower one.